2013
DOI: 10.1016/s2221-1691(13)60046-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological findings of concurrent poxvirus lesions and aspergillosis infection in canaries

Abstract: Canary pox has been known as the disease that can result in high losses in a short time, as a re-emerging disease that has not been present during recent years in canary flocks in Iran. So, the current paper provides useful information to prevent misdiagnosed of canary pox disease which can cause secondary mycotic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In general, diphtheritic and mixed pox infections present higher mortality rates than the cutaneous form [13,22,25], and it seems to cause higher mortality in wild birds than in poultry [26]. Septicemic infection is a rare expression of the disease [27], reported especially in canaries [2,28].…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, diphtheritic and mixed pox infections present higher mortality rates than the cutaneous form [13,22,25], and it seems to cause higher mortality in wild birds than in poultry [26]. Septicemic infection is a rare expression of the disease [27], reported especially in canaries [2,28].…”
Section: Pathologymentioning
confidence: 99%
“…It is, however, easier to monitor (and simpler to detect) the infection in captive than in wild populations. Mortality rates among captive birds may reach very high levels, and in many cases their death it is due to the systemic form of the disease, for example in canaries [28,[85][86][87].…”
Section: Outbreaks In Captive Wild Birdsmentioning
confidence: 99%
“…Mice bitten by CHIKV-infected mosquitoes showed significant increases in erythema readings on days 5 and 10, with a significant decrease noted on day 8 (Fig 2B), as compared to control mice bitten by uninfected mosquitoes. Presence of a rash can be variable among human disease [68,69,[71][72][73], however when present it is concomitant with fever spikes [74].…”
Section: Hu-nsg Mice Infected Via Mosquito Bite But Not By Needle Inoculation Demonstrate Signs Of Chikv Infectionmentioning
confidence: 99%
“…Many bird species experience life-long immunity if the immune system is not weakened and or the birds are not infected by different strains [ 27 , 28 ]. As shown in our example, secondary infections can occur and these may contribute to morbidity and mortality [ 29 – 31 ]. Similar to the example in shearwaters, Shivaprasad et al [ 30 ] reported evidence of poxvirus infection and secondary fungal pathogens in canaries ( Serinus canaria ).…”
Section: Discussionmentioning
confidence: 99%